2022
DOI: 10.1093/nop/npac022
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids use and neurocognitive functioning in patients with recurrent glioblastoma: Evidence from European Organization for Research and Treatment of Cancer (EORTC) trial 26101

Abstract: Background In patients with recurrent glioblastoma corticosteroids are frequently used to mitigate intracranial pressure and to improve patient neurological functioning. To date, in these patients no systematic studies have been performed to assess neurocognitive functioning (NCF) in relation to corticosteroid treatment. Methods Using baseline data (i.e., prior to randomization) of EORTC trial 26101 we performed regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…There is evidence from patients with HGG, however, that corticosteroid use is associated with improved recognition memory, which is likely to be due to resolution of cerebral oedema ( 49 ). The most robust evidence on corticosteroid use comes from an analysis of data collected from an RCT that effect of corticosteroid use on neurocognitive function in 321 patients with recurrent glioblastoma, using data from the European Organization for Research and Treatment of Cancer trial 26101; it found that patients on corticosteroids had worse neurocognitive function in all tested domains (memory, expressive language, visual-motor scanning speed, executive functioning) compared to those not on corticosteroids with significant inverse correlations between corticosteroid use and Hopkins Verbal Learning Test - Revised Free Recall and Delayed Recall scores ( 161 ). There is limited evidence of the effect of corticosteroids on cognition in patients with LGG, which is likely to be due at least in part to the fact that LGGs tend to cause cerebral oedema less frequently than many other tumor types.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence from patients with HGG, however, that corticosteroid use is associated with improved recognition memory, which is likely to be due to resolution of cerebral oedema ( 49 ). The most robust evidence on corticosteroid use comes from an analysis of data collected from an RCT that effect of corticosteroid use on neurocognitive function in 321 patients with recurrent glioblastoma, using data from the European Organization for Research and Treatment of Cancer trial 26101; it found that patients on corticosteroids had worse neurocognitive function in all tested domains (memory, expressive language, visual-motor scanning speed, executive functioning) compared to those not on corticosteroids with significant inverse correlations between corticosteroid use and Hopkins Verbal Learning Test - Revised Free Recall and Delayed Recall scores ( 161 ). There is limited evidence of the effect of corticosteroids on cognition in patients with LGG, which is likely to be due at least in part to the fact that LGGs tend to cause cerebral oedema less frequently than many other tumor types.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Caramanna showed that corticosteroid use was linked to poorer outcomes in memory function, expressive language, and executive function compared to GBS cohorts not using corticosteroids [97]. Accordingly, many clinical trials for GBS have corticosteroid use as an exclusion criterion.…”
Section: Corticosteroid Contraindicationsmentioning
confidence: 99%
“…In fact, the exhausted phenotype of immunocytes is developed due to the GB cells producing PD-L1 and 2, CTLA-4 and other proteins that inhibit T-cell activity receptors ( 144 ). The emergence of a new class of drugs that prevent PD-ligands from binding to T-cell receptors has attracted interest ( 145 ), but the effectiveness of nivolumab and other immune checkpoint inhibitors in the complex treatment of GB was revealed to be low ( 146 ), thus suggesting the existence of other causes of systemic immunosuppression.…”
Section: Csc Microenvironment Immunotherapy and Immunodeficiencymentioning
confidence: 99%